Identification of the CD200R1 promoter and the association of its polymorphisms with the risk of Parkinson's disease. (14th April 2020) - Lin, S.; He, L.; Shen, R.; Fang, F.; Pan, H.; Zhu, X.; Wang, M.; Zhou, Z.; Liu, Z.; Wang, X.; Fang, S.; Sun, X.; et al.
Abstract : Background and purpose: Neuroinflammation is known to be involved in the pathogenesis of Parkinson's disease (PD). Abnormal activation of microglia plays a key role in this pathological process. CD200R1 is a membrane glycoprotein that is expressed primarily on myeloid cells including microglia and is involved in the maintenance of microglia in a stationary state. Our previous study reported that the regulation of CD200R1 expression is altered in PD patients. Such alteration will lead to neuroinflammation and is related to the pathogenesis of PD. The possible role of promoter polymorphisms for abnormal CD200R1 expression in PD was examined in this study. Method: The UCSC database and dual‐luciferase assays were used to confirm the promoter region of CD200R1. The promoter of CD200R1 was sequenced in 457 PD patients and 520 matched healthy controls from the Chinese Han population. Dual‐luciferase assays were conducted to examine the promoter activity of CD200R1. Results: It was confirmed that the promoter of CD200R1 is located in the region 876–146 bp upstream of the coding DNA sequence. The frequencies of rs144721913 ( P  = 0.001) and rs72952157 ( P  = 0.022) in the promoter were significantly different between the PD group and control group. rs144721913 increases the risk of PD by approximately 14‐fold and rs72952157 by 2.6‐fold. The dual‐luciferase assay indicated that the rs144721913 T allele and the rs72952157 G allele reduced the transcriptional activity of the CD200R1 promoter. Conclusions: For the first time the promoter region of CD200R1 has been defined and two potential risk polymorphisms (rs144721913 and rs72952157) in the region for PD in Chinese Han populations have been reported.